Manejo de residuos de cosecha de maíz para el fortalecimiento de la cultura ambiental en comunidades rurales, cantón Tosagua-Manabí - Salvatierra Valdez, Vicky Nicolle (2025)
This study aimed to evaluate the management of corn harvest residues to strengthen environmental awareness in rural communities in Tosagua. The research focused on residents of the Primicia-Paraíso and Pitahaya communities, selecting men and women who cultivate corn based on specific criteria: residing in the community, having experience in corn farming, and demonstrating willingness to participate in the study. Through a methodological approach that included surveys and direct observation, current perceptions and practices related to agricultural waste management and its environmental impact were identified. An environmental education strategy was developed and implemented, encompassing affective, cognitive, conative, and active dimensions to promote sustainable and equitable waste management practices. The strategy included a practical component where community leaders participated in composting corn harvest residues. Post-implementation results showed increased awareness and willingness toward environmental conservation, reflecting significant changes in participants' perceptions and behaviors regarding corn residue management, suggesting progress toward sustainability and gender equity in agricultural practices in the region.